2004
DOI: 10.1177/1359105304045354
|View full text |Cite
|
Sign up to set email alerts
|

Recalling Sexual Partners: The Accuracy of Self-Reports

Abstract: Accuracy of recall of the number of sexual partners individuals had over a period of one month, three months, six months and one year was studied in a group of 285 young, single, heterosexual adults. Self-reports of the number of partners were obtained on a weekly basis and then compared with recall of behavior over longer time periods that overlapped the weekly measures. For individuals who claimed abstinence or who claimed to be monogamous, accuracy of recall was relatively high, especially at the shorter ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…Accordingly, the utility of such information remains open to question. This problem may be particularly acute with the self-reports of individuals whose overall pattern of sexual behavior would be described as higher risk for contracting HIV (Jaccard et al 2004). The advancement of knowledge in this field has also been impeded by lack of experimental studies.…”
Section: Critique Of Reviewed Literaturementioning
confidence: 98%
“…Accordingly, the utility of such information remains open to question. This problem may be particularly acute with the self-reports of individuals whose overall pattern of sexual behavior would be described as higher risk for contracting HIV (Jaccard et al 2004). The advancement of knowledge in this field has also been impeded by lack of experimental studies.…”
Section: Critique Of Reviewed Literaturementioning
confidence: 98%
“…49,50 Nevertheless, reliability studies evaluating test-retest and internal consistency have found relatively high agreement when surveys are administered under the same conditions using meaningful reference time intervals. 51,52 The validity of self-reported sexual behavior has been called into question by studies comparing selfreport with biologic outcomes such as STIs. 53,54 Dunne et al 53 found HPV DNA in 5% of women who reported never having had sex.…”
Section: Sexual Behaviormentioning
confidence: 99%
“…These community-based organizations provided HIV prevention and HIV primary care services; therefore, study participants could have received program interventions regarding disclosure practices. Data about sexual behavior is always self-reported data and, thus, can reflect errors in recall, deliberate falsification, intoxication during the interview process, and/or social desirability (Elliot, Huizinga, & Menard 1989;Jaccard et al, 2004). Finally, the study was limited by the characteristics of the sample, selectivity of the sample, and size of the sample.…”
Section: Discussionmentioning
confidence: 99%